Direct estimates of nitrogen abundance for Seyfert 2 nuclei - Dors, Oli L. (2024)
We derive the nitrogen and oxygen abundances in the narrow line regions (NLRs) of a sample of 38 local (z < 0.4) Seyfert 2 nuclei. For that, we consider narrow optical emission line intensities and direct estimates of the electron temperatures (Te-method). We obtain a new theoretical expression for the nitrogen ionization correction factor [ICF(N^+)] for NLRs. Applying this new ICF, we unexpectedly find that NLRs and disc HII regions exhibit similar ICF distributions. We find nitrogen abundances in the range 7.6 < 12+log(N/H) < 8.6(mean value 8.06±0.22) or 0.4 < (N/N⊙) <4.7,in the metallicity regime 8.3 < 12 + log(O/H) < 9.0. Our results indicate that the dispersion in N/H abundance for a fixed O/H value in AGNs of ∼0.2 dex agrees with that for disc H II regions with similar metallicity. We show that Seyfert 2 nuclei follow a similar (N/O)?(O/H) relation to the one followed by star-forming objects. Finally, we find that active galaxies called as "nitrogen-loud" observed at very high redshift (z > 5) show N/O values in consonance with those derived for local NLRs. This result indicates that the main star-formation event is completed in the early evolution stages of active galaxies.